Development of Augmented Reality Application for Chemical Bond - Jamil, Norsyahrina; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2021)
Chemical bond in Chemistry for secondary school education is one of the subjects in science course that are difficult to understand by most students. There are many factors that can cause this problem such as from learning method, the use of education tools and understanding level among students. Some of the problems are such as difficult to understand the concepts and process in chemical bond. The lack use of learning tools also creates less interest problems among the students. This study also about the use of augmented reality technology and how to implement it in learning. Augmented reality is a technology that allow user to interact with virtual object in real situation. Thus, an application Augmented Reality for Chemical Bond is developed as one of the solutions to solve the situation. The objective of this study is to create and develop the application and to test the functionality of the application. This application is combined with multimedia elements such as text, graphic and animation in providing explanation about the process of chemical bond. User Centered Design (UCD) development model is used as a guideline in the development of the study. Application of 3D Max Studio, Unity 2017.1.2, Adobe Photoshop CS6 and Vuforia will be use in the process of creating this product. It will be developed in form of android application to make it more user friendly. The Augmented Reality for Chemical Bond has gone through evaluation process by using feedback form and based from the data analysis from the evaluation, it has been showed that this application can be used by user with some improvement.